Chip-based generation of carbon nanodots via electrochemical oxidation of screen printed carbon electrodes and the applications for efficient cell imaging and electrochemiluminescence enhancement. Issue 21 (11th May 2015) - Xu, Yuanhong; Liu, Jingquan; Zhang, Jizhen; Zong, Xidan; Jia, Xiaofang; Li, Dan; Wang, Erkang
Abstract : A lab-on-a-chip electrochemical methodology to generate CNDs was developed. The CNDs can be used for efficient bioimaging and ECL sensor fabrication. Abstract : A portable lab-on-a-chip methodology to generate ionic liquid-functionalized carbon nanodots (CNDs) was developed via electrochemical oxidation of screen printed carbon electrodes. The CNDs can be successfully applied for efficient cell imaging and solid-state electrochemiluminescence sensor fabrication on the paper-based chips.